Programming Languages and Systems: 34th European Symposium on Programming, ESOP 2025, Held as Part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, Hamilton, ON, Canada, May 3–8, 2025, Proceedings, Part I (Lecture Notes in Computer Science, 2025)
The open access book set LNCS 15694 + LNCS 15695 constitutes the proceedings of the 34th European Symposium on Programming, ESOP 2025, which was held as part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, in Hamilton, Canada, during May 3-8, 2025. The 30 full papers included in the proceedings were carefully reviewed and selected from a total of 88 submissions. The proceedings also contain two short artifact reports. The papers focus on aspects of programming language research such as programming paradigns and styles; methods and tools to specify and reason about programs and languages; programming language foundations; methods and tools for implementation, concurrency and districution; and applications and emerging topics.